(untitled) (Margalla Papers, 2021)
Kashmiri female freedom fighters have remained at the forefront of the resistance movement, rallies, protest marches, and sit-ins. Unfortunately, their activism is invisible, and they have lagged during the dialogue process. The peace negotiations go awry to address the concerns, specific needs, approaches, views, and grievances of women during and after conflict situations. The UN has long been trying to address the concerns of women through varied resolutions, but the implementation of these mandates remains a formidable challenge. This research paper, therefore, aims to analyse the resistance and activism of Kashmiri women for their inalienable right of self-determination against the Indian Illegal Occupation of Jammu and Kashmir. The problem of Kashmiri women’s visibility in the resistance movement and their invisibility in the peace process is seen through the theoretical framework of Feminist Security Studies. For the textual interpretation and contextualization of data, Qualitative Content Analysis is employed. A way forward to address women’s issues and approaches during conflict situations is to implement the UN landmark Resolution-1325 on ‘Women, Peace, and Security’ by involving women in all stages of conflict resolution and post-conflict reconstruction. Bibliography Entry Raazia, Izzat, and Saqib ur Rehman. 2021. "Resistance of Women against Indian Illegal Occupation of Jammu and Kashmir: Their Invisibility during Peace Negotiations." Margalla Papers 25 (1): 92-102.